Analisis Persepsi Mahasiswa Terhadap Penggunaan Google Translate Sebagai Media Menerjemahkan - Annisa Putri; Zulkipli Lessy (Universitas Pahlawan Tuanku Tambusai, 2024)
The use of smartphones to assist students in learning is familiar. This tool is used in almost every student learning activity. For example, this tool is often used to browse the material needed or to translate Arabic material into Indonesian or vice versa. In an effort to understand Arabic material, students always try to translate sentences or paragraphs first from the original language to the target language. Google Translate is a service that is often used in the translation. This study describes students' perceptions of the use of Google Translate to translate Arabic materials. Interviews were used in collecting data. The subjects of this research are sixth semester students of Arabic Language Education Department with the consideration that they can already use Google Translate. The data shows that students' perceptions of the use of Google Translate in translation are positive, also that Google Translate provides many benefits, for example, students can translate faster and complete their assignments. Although there are still weaknesses in the translation results with Google Translate, Google Translate can save time in translating Arabic materials.